EXPOSITORY PREACHING: SOME QUESTIONS AND OBSERVATIONS - Molina, Carlos G. (Revista Hermenêutica (descontinuada), 2010)
RESUMO Esta variedade de pregação normalmente demanda umaboa dose de pesquisa acadêmica e, por causa disso, representatambém um desafi o no momento da apresentação, visto que,em geral, os pregadores precisam adaptar as informações aosouvintes. Contudo, é recompensador considerar seus benefíciosem termos de informação compartilhada, seu conteúdo bíblico, aaplicação contextualizada à audiência. ABSTRACT This variety of preaching normally demands a good dealon academic research and because of it represents also a deliverychallenge for preachers in adapting all the resulting informationto the hearers. However, it is rewarding to consider its benefi tsin terms of appropriated imparted information, its bible contextin the exegesis process and, probably one of the most diffi cultachievement for any sermon type, specially for the expository:the bullet(s) contextualized application(s) for the audience.